2019
DOI: 10.1002/ird.2339
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Drainmod‐s to Predict Drainage Water Salinity and Groundwater Table Depth During Winter Cropping in Heavy‐Textured Paddy Soils

Abstract: Simulation models can quickly and cost‐effectively describe various aspects of management practices in newly reclaimed agricultural soils. In this research, the capability of the DRAINMOD‐S model was evaluated to predict the salinity of the subsurface drainage effluents in a newly subsurface drained paddy field during winter cropping. Measurements of groundwater table depths and drainage water salinity were taken in three conventional subsurface drainage systems at the Sari Agricultural Sciences and Natural Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Saline soils are prevalent globally, particularly in arid and semi-arid regions where shallow groundwater evaporation is the dominant factor in soil salinization (Chandio et al, 2013). Moreover, soil salinization in arid areas is influenced by the shallow groundwater level and rapid fluctuation (Ibrahimi et al, 2014), groundwater abstraction (McCallum et al, 2013), and the irrigation of farmland (Chen et al, 2020) and drainage water (Davoodi et al, 2019), which indirectly affects the process of soil salinization. Effective management of groundwater and surface water has been found to be a key approach for reducing soil salinization (Machado and Serralheiro, 2017;Li et al, 2018;Yu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Saline soils are prevalent globally, particularly in arid and semi-arid regions where shallow groundwater evaporation is the dominant factor in soil salinization (Chandio et al, 2013). Moreover, soil salinization in arid areas is influenced by the shallow groundwater level and rapid fluctuation (Ibrahimi et al, 2014), groundwater abstraction (McCallum et al, 2013), and the irrigation of farmland (Chen et al, 2020) and drainage water (Davoodi et al, 2019), which indirectly affects the process of soil salinization. Effective management of groundwater and surface water has been found to be a key approach for reducing soil salinization (Machado and Serralheiro, 2017;Li et al, 2018;Yu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Computational hydrologic modeling platforms, e.g. DRAINMOD [60], have been widely used to predict salinity of drainage water used in irrigation [61]. A number of numerical models and finite element analyses have also been used for salinity prediction, e.g., SUTRA, RMA-10 [62].…”
Section: Introductionmentioning
confidence: 99%
“…According to Bahçeci and Nacar (2009), in studies in southeastern Turkey, the use of drainage promoted an 80% reduction in salinity in the 0-20 cm layer of the soil. Davoodi, Darzi-Naftchali and Aghajani-Mazandarani (2019), in studies in northern Iran, observed the removal of up to 586 kg ha -1 of salts in subsurface drainage systems. A study conducted in the Curu-Pentecoste Irrigated Perimeter, Ceará, associating the installation of subsurface drainage with management practices (subsoiling and use of soil conditioners), demonstrated the reclamation of a saline-sodic soil, reduction of waterlogging problems, and the improvement in the growth of coconut trees (SOUSAet al, 2011(SOUSAet al, , 2014 (Figure 2).…”
Section: Drainage Strategies For Leaching Salts From the Soilmentioning
confidence: 99%